The use of real-time feedback to improve kinematic marker placement consistency among novice examiners - Macaulay, Charles A.J.; Osis, Sean T.; Clermont, Christian; Ferber, Reed (Gait & posture, 2017)
•Marker placement inconsistency is the largest source of error in kinematic gait analysis.•Novel software provides real-time placement feedback regarding marker placement.•Use of the software improves consistency of gait kinematics for a group of novice examiners.•This effect was also seen during a one-week follow-up session. Marker placement deviation has been shown to be the largest source of error in gait kinematic data, limiting the ability of clinicians and researchers to conduct between-day or between-center investigations. Prior marker-placement standardization methods are either impractical for a clinical setting or rely on expert marker placement. However, a recently developed, real-time feedback tool has been developed and shown to improve marker placement and downstream kinematic calculations. The purpose of this study was to determine whether this real-time marker-placement tool could improve the consistency of gait kinematic data collected by a group of novice examiners. Twelve novice examiners identified anatomical landmarks and placed retroreflective markers on a single subject. For each examiner, a running trial was analyzed separately using two static trials: (1) PRE and (2) POST implementation of the feedback tool. The protocol was repeated a second time, one week later. Between-examiner consistency was represented by the 95% confidence interval (CI) of the mean joint angles for the entire stride, and compared between the PRE and POST conditions. The POST feedback trials showed an average 27.45% reduction of the 95%CI range for eight out of nine joint angles on day one, and an average 24.73% for five out of nine joint angles on day two, compared to POST. The results indicate a real-time feedback tool improves the consistency in marker placement for novice users.